Dense Wavelength Division Multiplexing Optical Network System - Md. Masud Rana; Muhammad Abdul Goffar Khan (Institute of Advanced Engineering and Science, 2012)
In this paper, a dense wavelength division multiplexing (DWDM) system with 64 modulated channels 50 GHz spacing covering 25.2-nm bandwidth has been demonstrated. When optical signals are to travel over long distances, it’s be faded and spread out. So, it is necessary to strengthen the signal at intervals. To keep the signal strength at same level in the DWMD system, Er-doped fiber amplifier (EDFA) has been used. The EDFA provides a gain across the bandwidth with 10 dB average gain and a gain shape variation peak-to-peak of about 1 dB. OptSim’s physical EDFA model has been used for DWMD systems.DOI:http://dx.doi.org/10.11591/ijece.v2i2.202